'Black Box' in flux: Locating the literary work between media. (1st June 2015) - Andersen, Tore Rye
Traditionally, the printed book has been the preferred mode of delivery for literature, to such an extent that the book's status as a medium has been practically invisible. However, recent studies have demonstrated that the mediality of the book affects the way we read. The interpretation of literature is not just a matter of scrutinizing the text itself but of analysing the complex interplay between form, content and medium. In 2012 Jennifer Egan published the story 'Black Box' via Twitter. The story has subsequently been published in various other media, such as magazines, printed books and as an audiobook. This multimodal publication history necessitates new analytical strategies that can investigate what happens to our notions of a literary work when the literary text appears in several media at once. Taking off from an analysis of 'Black Box' and its various embodiments and drawing on John Bryant's concept of 'the fluid text' the article discusses what happens to the literary work when it is dispersed between various media.